Innovative approaches to customs inspections of participants in foreign economic activity - Yu. E. Gupanova; A. S. Lemak (Управление)
With the adoption of the Strategy for the Development of the Customs Service of the Russian Federation until 2030, one of the priorities for customs authorities has become the introduction of new approaches to the organization and conduct of customs control after the release of goods.The purpose of the research paper is to identify problematic aspects of the implementation of customs inspection technology and to substantiate innovative approaches to their implementation. The research methodology is based on the use of methods of analysis, synthesis, generalization, comparison and description, which allowed a comprehensive study of the object.The paper proposes a new approach, which provides for the centralization and concentration of control functions of customs control after the release of goods in authorized departments. This approach will improve not only the efficiency of the customs authorities for the implementation of supervisory functions after the release of goods but also the quality of customs administration in terms of creating a unified network of electronic customs offices, ensure the achievement of balance in the application of customs procedures facilitating and monitoring the implementation of foreign economic activity.The authors define the main directions for improving the technology of customs inspections to ensure the implementation of the new approach. The formed recommendations based on the results of the study can be used in the practical activities of the customs authorities of the Russian Federation.